Stanniocalcin-1 protein expression profile and mechanisms in proliferation and cell death pathways in prostate cancer. (15th February 2020) - Costa, Bruna Pasqualotto; Schein, Vanessa; Zhao, R.; Santos, Andressa Schneiders; Kliemann, Lucia Maria; Nunes, Fernanda Bordignon; Cardoso, J.C.R.; Félix, Rute Castelo; Canário, A.V.M.; Brum, Ilma Simoni; Branchini, Gisele
Abstract: Prostate cancer (PCa) is one of the most prevalent male tumours. Stanniocalcin-1 (STC1) is a glycoprotein and, although the role of STC1 in human cancer is poorly understood, it is suggested to be involved in the development and progression of different neoplasms. This study investigated the protein expression profile of STC1 in PCa and benign prostatic hyperplasia (BPH) samples and STC1 signalling during cell proliferation and cell death in vitro using cell lines. We found higher levels of STC1 in PCa when compared to BPH tissue and that STC1 inhibited forskolin stimulation of cAMP in PC-3 cells. A monoclonal antibody against STC1 was effective in reducing cell proliferation, in promoting cell cycle arrest, and in increasing apoptosis in the same cells. Since STC1 acts as a regulator of prostatic tissue signalling, we suggest that this protein is a novel candidate biomarker for prostate tumour clinical progression and a potential therapeutic target. Highlights: Expression levels of STC1 in PCa were significantly higher in more aggressive tumours. STC1 inhibits cAMP production in PCa cells in vitro. Specific anti-STC1 antibody treatment reduces cell proliferation in PCa cell line. Specific anti-STC1 antibody treatment increases apoptosis in PCa cell line. STC1 signalling can be a potential target for PCa therapies.